Targeting androgen receptor-independent pathways in therapy-resistant prostate cancer - Lingfan Xu; Junyi Chen; Weipeng Liu; Chaozhao Liang; Hailiang Hu; Jiaoti Huang (Asian Journal of Urology)
Since androgen receptor (AR) signaling is critically required for the development of prostate cancer (PCa), targeting AR axis has been the standard treatment of choice for advanced and metastatic PCa. Unfortunately, although the tumor initially responds to the therapy, treatment resistance eventually develops and the disease will progress. It is therefore imperative to identify the mechanisms of therapeutic resistance and novel molecular targets that are independent of AR signaling. Recent advances in pathology, molecular biology, genetics and genomics research have revealed novel AR-independent pathways that contribute to PCa carcinogenesis and progression. They include neuroendocrine differentiation, cell metabolism, DNA damage repair pathways and immune-mediated mechanisms. The development of novel agents targeting the non-AR mechanisms holds great promise to treat PCa that does not respond to AR-targeted therapies. Keywords: Prostate cancer, Therapeutic resistance, Androgen receptor, Neuroendocrine, Cancer metabolism, DNA damage repair